Lobetyolin induces apoptosis of colon cancer cells by inhibiting glutamine metabolism. Issue 6 (28th January 2020) - He, Wei; Tao, Weiwei; Zhang, Feng; Jie, Qian; He, Yun; Zhu, Wei; Tan, Jiani; Shen, Weixing; Li, Liu; Yang, Ye; Cheng, Haibo; Sun, Dongdong
Abstract: The purpose of the present study was to evaluate the anti‐cancer property of Lobetyolin on colorectal cancer and explore its potential mechanism. Lobetyolin was incubated with HCT‐116 cells in the absence or presence of ASCT2 inhibitor Benser or p53 inhibitor Pifithrin‐α. The levels of glutamine, glutamic acid, α‐ketoglutarate, ATP and GSH were determined to measure the glutamine metabolism. Annexin V‐FITC/PI staining and TUNEL assay were applied to estimate the apoptotic condition. The levels of ASCT2 were examined by RT‐qPCR, Western blot and immunofluorescence staining. The expressions of cleaved‐caspase‐3, caspase‐3, cleaved‐caspase‐7, caspase‐7, cleaved‐PARP, PARP, p53, p21, bax and survivin were detected using Western blot analysis. As a result, the treatment with Lobetyolin effectively induced apoptosis and glutamine metabolism in HCT‐116 cells through ASCT2 signalling. The inhibition of ASCT2 reduced the glutamine‐related biomarkers and augmented the apoptotic process. We further found that the effect of Lobetyolin on HCT‐116 was related to the expressions of p21 and bax, and transportation of p53 to nucleus. The inhibition of p53 by Pifithrin‐α promoted the inhibitory effect of Lobetyolin on ASCT2‐mediated apoptosis. Lobetyolin also exerted anti‐cancer property in nude mice. In conclusion, the present work suggested that Lobetyolin could induce the apoptosis via the inhibition of ASCT2‐mediated glutamine metabolism, which was possibly governed by p53.